Debate: Lessons learned in lockdown – a one‐day remotely delivered training on low‐intensity psychological interventions for common mental health conditions. Issue 3 (16th July 2020) - Batchelor, Rachel; Catanzano, Matteo; Kerry, Ellie; Bennett, Sophie D.; Coughtrey, Anna E.; Liang, Holan; Curry, Vicki; Heyman, Isobel; Shafran, Roz
Abstract : The coronavirus pandemic has highlighted the need for remote technologies to be used in child and adolescent mental health services. With the UK being placed in lockdown one week before a scheduled 'face‐to‐face' low‐intensity CBT training day due to COVID‐19, there was a need for rapid adaptations to be made to the content, structure and format of a training day for practitioners in mental health services, to suit the online environment. The content covered the core areas of low‐intensity CBT in children and adolescents. Findings showed that the one‐day low‐intensity training day increased knowledge and understanding in all key areas measured, and was positively received, providing further evidence for the effectiveness and acceptability of remote delivery. Given discussed benefits of remote delivery, as well as rapid developments in technologies helping to address some of the challenges raised, going forward, remote delivery could continue to be beneficial for increasing access to much needed evidence‐based interventions.